Effect of Oxidative Stress in Elite Athletes and Characterization of Sodium Dodecylsulfate Polyacrylamide Gel Electrophoresis - Zeliha Baştürk, Mehmet Kiliç, Nuri M. Embiyaoğlu, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The aim of this study was to examine the protein characterization of oxidative stress effects in elite athletes with the SDS-Page method. Material and Methods: 28 male athletes voluntarily participated in the study, competing in 4 different branches (Cycling – n = 7, Boxing – n = 7, Wrestling – n = 7, Teaekwondo – n = 7), with an average age of 21-25 years and actively doing sports. The study protocol was approved by the ethics committee of Selçuk University School of Physical Education and Sports. Blood samples were taken three times as a result of resting, anaerobic and aerobic strength tests. All serums obtained were protein isolated using the EURX brand Gene Matrix Universal DNA/RNA Protein Purifacition kit in the molecular biology laboratory of the Department of Biology, Faculty of Science, Selcuk University. Proteins were characterized by BIORAD Mini Protean Electrophoresis System SDS-Page method with THERMO PagerulerPrestained Protein Ladder marker. Results: Bands with a size of 200 kDa, which were evaluated as immunoglobulins, were found in cycling rest, boxing resting and maximal, wrestling maximal and submaximal values. In addition, all three status values of the bicycle group are similar. Boxing group is the most distinctive group in terms of protein profile and content. While the maximal and submaximal values ​​were similar in the wrestling group, fainter protein bands were observed in the resting states. Although the resting and maximal protein profiles and contents of the taekwondo group were similar, it can be said that protein bands are more prominent in submaximal exercise results. As a result; The serum protein concentrations of the athlete groups are similar. While the similarities of the cycling, boxing and taekwondo groups were more evident in terms of protein content and profiles, the maximal and submaximal post-exercise values of the wrestlers were similar. Conclusions: We can associate the differences between the groups of athletes with the intensity and intensity of the exercise they have done. It can be said that the protein fraction is lower after maximal exercises for cyclists and submaximal for boxers and taekwondoers. The number of bands is higher and more prominent in the boxing group compared to the other groups. In the wrestling group, on the other hand, while the maximal and submaximal protein characterizations were similar, fainter bands were observed in the resting profiles. The reason for this change is thought to be due to oxidative stress as well as genetic differences and/or acute or chronic physiological changes specific to the branch.